Generating the perception of choice: the remarkable malleability of option‐listing. Issue 7 (3rd August 2018) - Toerien, Merran; Reuber, Markus; Shaw, Rebecca; Duncan, Roderick
Abstract: The normative view that patients should be offered more choice both within and beyond the UK's National Health Service (NHS) has been increasingly endorsed. However, there is very little research on whether – and how – this is enacted in practice. Based on 223 recordings of neurology outpatient consultations and participants' subsequent self‐reports, this article shows that 'option‐listing' is a key practice for generating the perception of choice. The evidence is two‐fold: first, we show that neurologists and patients overwhelmingly reported that choice was offered in those consultations where option‐listing was used; second, we demonstrate how option‐listing can be seen, in the interaction itself, to create a moment of choice for the patient. Surprisingly, however, we found that even when the patient resisted making the choice or the neurologist adapted the practice of option‐listing in ways that sought acceptance of the neurologist's own recommendation, participants still agreed that a choice had been offered. There was only one exception: despite the use of option‐listing, the patient reported having no choice, whereas the neurologist reported having offered a choice. We explore this deviant case in order to shed light on the limits of option‐listing as a mechanism for generating the perception of choice.